1965
DOI: 10.1002/cpt196566716
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl chlorophenoxyisobutyrate (CPIB) effects in juvenile‐onset diabetes mellitus

Abstract: Ethyl chlorophenoxyisobutyrate (CPIB) effects in iuvenile-onset diabetes mellitus Ethyl-a (p-chlorophenoxy)isobutyrate (Atromid-S or CPIB) Department of Medicine, University of Pittsburgh, and the Medical Center and Shadyside HospitalsEthyl-a (p-chlorophenoxy )iso butyra te (CPIB or Clofibrate) available with and without androsterone as Atromid and Atromid-S, respectively, reduces hyperlipidemia in man toward or to normal,2, 3, 4, parent amelioration of diabetes has been observed chiefly or entirely in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1969
1969
1979
1979

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…In patients with coronary heart disease, clofibrate has been reported not to modify (Schwandt, Weisweiler, Neureuther & Wilkening, 1976) or to significantly reduce fasting blood glucose (Enger et al, 1977;Csogor & Bornemisza, 1977). As a rule, fasting blood glucose was unchanged in diabetic patients (Danowski, Cohn, Limaye, Novak, Saul, Sunder & Moses, 1965;Danowski Novak, Saul, Vester & Moses, 1966;Jain, Ryan, McMahon, 1975;Pontirelli, Viberti & Pozza, 1976) but in one study (Ferrari et al, 1977), fasting blood glucose significantly decreased after 5 days of clofibrate administration. In 22 diabetic patients, 11 of whom being insulin-dependent, clofibrate induced a significant reduction in glycosuria (Csogor & Bornemisza, 1977).…”
Section: Discussionmentioning
confidence: 92%
“…In patients with coronary heart disease, clofibrate has been reported not to modify (Schwandt, Weisweiler, Neureuther & Wilkening, 1976) or to significantly reduce fasting blood glucose (Enger et al, 1977;Csogor & Bornemisza, 1977). As a rule, fasting blood glucose was unchanged in diabetic patients (Danowski, Cohn, Limaye, Novak, Saul, Sunder & Moses, 1965;Danowski Novak, Saul, Vester & Moses, 1966;Jain, Ryan, McMahon, 1975;Pontirelli, Viberti & Pozza, 1976) but in one study (Ferrari et al, 1977), fasting blood glucose significantly decreased after 5 days of clofibrate administration. In 22 diabetic patients, 11 of whom being insulin-dependent, clofibrate induced a significant reduction in glycosuria (Csogor & Bornemisza, 1977).…”
Section: Discussionmentioning
confidence: 92%
“…In a study of young diabetic patients taking clofibrate for three months, no change was noted in the PBI or T3 red cell uptake. 4 Mogensen,!l however, noted a slight but significant reduction in T3 red cell uptake following clofibrate administration for 3 days, which is compatible with increased binding of thyroid hormones by protein carriers. In vitro studies with clofibrate have shown an increase in TBG binding capacity for thyroxine.…”
Section: D'iscussionmentioning
confidence: 86%
“…Data obtained in the first few months and the first year of therapy have been published previously. 4,7,27 The findings herein summarized are based on mean values recorded in the two groups prior to and at the end of 2 to 5 years of therapy. Measurements obtained several times each year were pooled and expressed as the mean value for that interval of time.…”
Section: Clinical Pharmacologymentioning
confidence: 99%